Analysis of the Dispute Settlement of the Authority of State Institutions Based on the Constitution of the Republic of Indonesia - Arifin Tumuhulawa; Roy Marthen Moonti; Yusril Katili (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Objective of study is to identify and analyze dispute resolution on the authority of state institutions whose authority is granted by the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) by the Constitutional Court as regulated in the constitution, the fourth amendment to Article 24C paragraph 1 UUD 1945. By using a normative juridical research method and analytical descriptive, with a statutory approach, a conceptual approach, and a casuistic approach. Disputes on authority between state institutions are caused by the first; an inadequate system to regulate and oversee relations between existing institutions, secondly; Different interpretations of a provision, third; The mechanism of checks and balances on an equal relationship is possible in the implementation of the authority of each state institution, differences and/or disputes arise in interpreting the mandate of the Constitution, fourthly there is overlapping authority, and fifthly, there is authority of state institutions whose authority is obtained from the constitution or the 1945 Constitution carried out by other state institutions. Disputes involving state institutions that are not the main state organs (constitutional state organs) can be resolved at the Constitutional Court on the condition that the state institutions have constitutional importance.